THE COMPARISON OF CIGARETTE CONSUMPTION TOWARDS SEMEN ANALYSIS IN ANDROLOGY POLYCLINIC OF DR. SOETOMO GENERAL ACADEMIC HOSPITAL, SURABAYA, INDONESIA IN 2017 - Yohanes Widyakusuma Eka Saputra; Kristanti Wanito Wigati; Rina Yudiwati; Ni Wajan Tirthaningsih (Majalah Biomorfologi, 2021)
Background: The habit of smoking tobacco is a lifestyle that has become a necessity for some people. Sometimes, social needs is the main reason for someone to have a smoking habit. Based on this problem, the level of cigarette consumption in the community has increased. Nowadays, the total number of couples visiting an infertility clinic is on the rise. This have led to an assumption among the community that smoking tobacco is one of the main factors causing male infertility. Objective: to compare light smokers and heavy smokers towards the results of semen analysis in infertile male patients. Materials and Methods: This study was an observational analytics, with a retrospective-cross sectional. The instrument used in this study was taken from medical records of the patients who visited the Andrology Clinic of Dr. Soetomo General Academic Hospital, Surabaya, Indonesia, for the period from January to December 2017. The observed semen analysis parameters were concentration, motility, and morphology for microscopic examination and liquefaction, pH, and volume for macroscopic examination, by following the inclusion and exclusion criteria. Results: Ninety-two samples of infertile male participants (50 light smokers and 42 heavy smokers) were included in this study. Semen analysis on its concentration, motility, spermatozoa morphology, as well as liquefaction, pH, and volume) towards the number of cigarette consumption showed no significant difference (p>0.05) between light smokers and moderate smokers. Conclusion: There was no significant difference between the light smoker and heavy smoker groups on the results of the semen analysis.